Analisis Hukum Islam Terhadap Pembatalan Putusan PA Bangkalan No.0774/Pdt.G/2013/PA.Bkl Oleh Putusan PTA Surabaya No.0014/Pdt.G/2014/Pta.Sby Tentang Perselisihan dan Pertengkaran Terus Menerus Sebagai Alasan Perceraian - Ali Ibrohim; Sam'un (AL-HUKAMA, 2017)
Abstract: The reasons for divorce in law of marriage in Indonesia, which has been formalized in Law no. 1 year 1974 and Compilation of Islamic Law, can be searched in munakahat Islamic jurisprudence. It is bacause both of material and formal law in Religious Courts are very accommodating to the implementation of Islamic Law, either directly or implicitly. During the time, the difference interpretation about the provisions of Article 39 paragraph (2) of Law No. 1 Year 1974 about marriage jo Article 19 Government Regulation No. 9 of 1975 jo Article 116 letter (f) Compilation of Islamic Law on continuous disputes always becomes polemic. Even the reasons for this dispute or argument dominate divorce decisions at various levels of the Religious Courts. Though there is no clear measure of this reason so it is natural that the Bangkalan Religious Court’s decision NO.0774/PDT.G/2013/PA.bkl was canceled by the Surabaya Religious High Court for the reason of this kind of divorce. Therefore it is necessary to prove that the decision taken by the judge on dispute or argument has met the criteria of nusyuz and syiqaq. In addition, the theory of benefit and maqasid of Shari’ah are also important for the consideration. This article is a review of the judge’s consideration of the Surabaya Religious High Court in canceling the decision of the Bangkalan Religious Court which decided a divorce by the reasons of continuous dispute and quarrel.